Gait velocity, attention and exercise in Parkinson's disease - Gobbi, Lilian Teresa Bucken [UNESP]; Vitorio, Rodrigo [UNESP]; Teixeira-Arroyo, Claudia [UNESP]; Lirani-Silva, Ellen [UNESP]; Rinaldi, Natalia Madalena [UNESP]; Barbieri, Fabio Augusto [UNESP]; Pereira, Marcelo Pinto [UNESP]; Santos, Paulo Cezar Rocha [UNESP]; Batistela, Rosangela Alice [UNESP] (My University, 2012)
In addition to pharmacological therapy, different modes of interventions has been purposed and applied for people with Parkinson's disease (PD). The results of these interventions have been shown improvements in their quality of life and functional mobility, among others. This study aimed to identify the effects of a 6-month, multimodal exercise program on stride velocity and attentional outcomes in PD patients and to observe the relationship between these dependent variables. Twenty-one patients with idiopathic PD were assessed before and after the multimodal exercise program (three times a week, one hour per session). Outcome measures included the stride velocity of self-paced walking and score (number of right/wrong answers) in the attention test of Wechsler Adult Intelligence Scale (WAIS-III). Gait velocity and the number of errors at WAIS-III improved after the enrollment in the multimodal exercise program. It was observed a significant positive relationship between gait velocity and number of right answers at WAIS-III before the multimodal exercise program. These findings suggest that PD patients with higher attentional levels show less impairment in gait velocity. Although physical exercise was effective to improve motor and cognitive characteristics of PD patients, further study in the form of randomized controlled trial would be required to establish effectiveness of the multimodal exercise program. © 2012 Nova Science Publishers, Inc. All rights reserved.